Recria de novilhas recebendo farelo de arroz em pastagem de papuã - Negrini, Mateus (2016)
The work was developed with the objective to evaluate the intake of forage and beef heifers performance from 15 to 18 months old, grazing in Alexandergrass (Urochloa plantaginea (Link) Hitch) under rotational grazing method, receiving rice bran (FAI) as a supplement, at different levels (0, 0.5 and 1.0% of body weight (BW)). The experimental design was completely randomized with repeated measures over time. The use of FAI increased the total intake of dry matter (DM), total intake of crude protein and total digestible nutrients in relation to heifers exclusively on pasture. The heifers that received 1.0% PC FAI reduced the intake of forage DM increasing by 18% stocking rate (SR) and 27% BW gain per hectare (BWA) compared with the system exclusively in pasture. In the system in which the heifers received FAI at 0.5% of BW the SR and BWA were similar to other systems. In this feed system daily weight gain 18% higher than heifers exclusively on pasture and similar gain to the use of FAI at 1.0% of BW were observed. In Alexandergrass pasture under rotational grazing, using FAI at 0.5% of BW for beef heifers from 15 to 18 months of age is recommended to promote higher production response when compared to heifers exclusively on pasture and similar production when provided FAI at 1.0% of BW.